Hubungan Kualitas Layanan Administrasi dengan Tingkat Kepuasan Siswa Pendidikan Dasar di UPT SDN Karanganyar Kota Pasuruan Tahun Ajaran 2024/2025 - Febhy Dwi Rachmanda (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the influence of the quality of educational administration services on the satisfaction of fourth, fifth, and sixth-grade students at UPT SDN Karanganyar, Pasuruan City, in the 2024/2025 academic year. Service quality was measured using five SERVQUAL dimensions (tangibles, reliability, responsiveness, assurance, and empathy), while student satisfaction was measured through indicators of expectation fulfillment, accessibility, service speed, staff attitude, and overall satisfaction. A sample of 101 students was drawn using simple random sampling from a population of 135 students. Data analysis included validity and reliability tests, classical assumption tests, and simple linear regression. The results showed that the quality of educational administration services had a positive and significant effect on student satisfaction, with the regression equation Y = 15.322 + 0.768X